A CFD STUDY ON HEAVY DUTY DI DIESEL ENGINE TO ACHIEVE ULTRA-LOW EMISSIONS - (:unkn) unknown (AMER SOC MECHANICAL ENGINEERS, 2010)
Nowadays, automotive industries focused on clean diesel combustion in their combustion processes are investigated for their potential to achieve near zero particulate and NOx (Nitrogen oxides) emissions. Their main disadvantages are increased level of unburned hydrocarbons (HC) and carbon monoxide (CO) emissions, combustion control at high load, power output and limited operating range. The simulation of the air flow, spray and combustion in an internal combustion engine were prepared for a single cylinder of a nine-liter, six cylinder diesel engine. Many times the geometry is complex because moving pistons and valves are involved, which makes it difficult to generate structured mesh. In-cylinder spray-air motion interaction, a Lagrangian multiphase model has been applied in a heavy-duty CI engine under direct injection conditions. A comprehensive model for atomization of liquid sprays under high injection pressures has been employed. Three dimensional CFD calculations of the intake, compression and power strokes have been carried out with different spray angle, spray profile and start of injection. A new combustion model ECFM-3Z (Extended Coherent Flame Model) developed at IFP is used for combustion modeling. Finally, a calculation on an engine configuration with compression, spray injection and combustion in a direct injection Diesel engine is presented. In this study, exhaust emissions, and particularly the emission of NOx, CO and soot derived from premixed combustion are investigated, and the relationship between combustion and emission characteristics are showed. The calculated CFD simulation in different combustion cases was compared. The cases were prepared by changing the parameters: start of injection, spray angle and spray profile. Modeling of combustion proposed in the present study can be outlined as follows. NOx concentration is decreased by combustion of a over lean-mixture modeled by the pre- injection. Most of pre-mixture is combusted by main-injection, and therefore the amount of pre-injection and main-injection come into prominence. The results are greatly in agreement qualitatively with the previous experimental and computational studies in the literature.
Keywords: HCCI; CFD; spray; combustion; MODELS